Validation of the Chinese Patient Participation Scale (PPS-C) in Internal Medicine Patient: A Psychometric Study - Wang W; He H; Bao L; Wu M (Patient Preference and Adherence, 2025)
Wenqin Wang,1 Hongmei He,2 Liyun Bao,2 Minjuan Wu1 1School of Medicine, Quzhou College of Technology, Quzhou, People’s Republic of China; 2Department of Nursing, The First People’s Hospital of Hangzhou Lin’an District, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Minjuan Wu, Quzhou College of Technology, No. 18 Jiangyuan Road, Baiyun Street, Kecheng District, Quzhou, 324000, People’s Republic of China, Tel +86 17764554463, Email wuminjuan83@126.comObjective: To translate the Patient Participation Scale (PPS) into Chinese and evaluate its psychometric properties among internal medicine patients in a tertiary hospital in China, providing a reliable tool for enhancing patient participation in healthcare decisions.Background: Patient participation is critical for patient-centered care, widely proven to enhance healthcare quality and improve health outcomes. While China increasingly recognizes the importance of patient participation in clinical decision-making, evidence-based interventions remain limited, partly due to the lack of validated measurement tools. The original PPS has demonstrated promise in assessing patient participation, but its application in China requires cultural adaptation to ensure conceptual and linguistic equivalence.Design: A cross-sectional study.Methods: The Brislin’s translation model was followed to translate the PPS. A convenience sample of 457 internal medicine patients in a tertiary hospital was recruited. Validity was calculated by content validity, construct validity, concurrent validity, and convergence validity. Reliability was analyzed through internal consistency reliability and test–retest reliability.Results: The content validity index was 0.914. The confirmatory factor analysis indicated a significantly good fit for a four-factor model (χ2/df = 3.826, RMSEA = 0.079, CFI = 0.922, GFI = 0.862, AGFI = 0.825, NFI = 0.897, SRMR = 0.043, TLI = 0.910). The Cronbach’s alpha was 0.953, and the dimensions ranged from 0.759 to 0.910. The positive correlation between the Chinese version of the Patient Participation Scale (PPS-C) and Inpatients Involvement in Medication Safety Behavior Scale indicated acceptable convergent validity (r = 0.454). The positive correlation between the PPS-C and Health Literacy Management Scale indicated acceptable concurrent validity (r = 0.217). Scores differed significantly by household income and marital status. Test–retest reliability was 0.906.Conclusion: The PPS-C has good reliability and validity, which can be applied to the assessment of the participation levels of internal medicine patients in China.Keywords: cross-cultural adaptation, quality of life, patient participation, reliability, validity